2014
DOI: 10.1055/s-0034-1376886
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Meshes used in Hernia Repair: A Comprehensive Review of Synthetic and Biologic Meshes

Abstract: The current standard of practice for the treatment of ventral hernias is the use of permanent synthetic mesh material. Recently, biologic meshes have become more frequently used. Most meshes exhibit biomechanical properties over the known abdominal wall thresholds. Augmenting strength requires increasing amounts of material contributing to more stiffness and foreign body reaction, which is not necessarily an advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 48 publications
0
20
1
Order By: Relevance
“…28 Bleichrodt et al repaired contaminated abdominal wall defects in rats with using PP mesh and PTFE mesh, and at the end of the follow-up period, they found that 76.2% of the PTFE mesh group and 66.7% of the PP mesh group had SSI, and there was no statistically significant difference between the two groups in terms of the SSI rate. 15 In the current study, no adhesion was seen in any of the rats in the PTFE and ePTFE groups and all were found to develop SSI; therefore, the SSI rates of these two groups differed from that of the PP mesh group. Furthermore, the SSI rates were high in all study groups due to the mesh being applied to a contaminated wound.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…28 Bleichrodt et al repaired contaminated abdominal wall defects in rats with using PP mesh and PTFE mesh, and at the end of the follow-up period, they found that 76.2% of the PTFE mesh group and 66.7% of the PP mesh group had SSI, and there was no statistically significant difference between the two groups in terms of the SSI rate. 15 In the current study, no adhesion was seen in any of the rats in the PTFE and ePTFE groups and all were found to develop SSI; therefore, the SSI rates of these two groups differed from that of the PP mesh group. Furthermore, the SSI rates were high in all study groups due to the mesh being applied to a contaminated wound.…”
Section: Discussioncontrasting
confidence: 42%
“…1,[5][6][7][8][9][10][11][12][13] Researchers have yet to reach a consensus regarding the type of material to be used. [14][15][16] A Bogota bag is often preferred because it is far more inexpensive and available compared to the other materials; however, PTFE or PP mesh is often used to close the abdominal wall defect after the removal of the Bogota bag.…”
Section: Introductionmentioning
confidence: 99%
“…This antiadhesion effect of PCO mesh could be ascribed to the smooth surface of collagen coating, which did not provide any physical anchor points for adhesive tissue . However, several studies have reported that PCO mesh may have some complications such as seroma and infections, while lightweight PP mesh can resist to such complication because of its large pore structure . The PDA coating did not alter the large pore structure of lightweight PP mesh and preserved its good properties including high permeability and biocompatibility.…”
Section: Discussionmentioning
confidence: 98%
“…The cost of PP/PDA is estimated to be US dollar (USD) 3 cm −2 , which proves economically competitive with the advanced meshes used for ventral hernia repair today, including PCO (USD 20 cm −2 ) and biological meshes (more than USD 60 cm −2 ). Further investigation indicated that PCO mesh, one of the synthetic meshes, had more complications of infection and recurrence than other meshes . Moreover, it was demonstrated that expanded polytetrafluoroethylene (ePTFE) hernia mesh still induced infection, seroma, and shrinkage due to its masked and blocked pores and inflammatory response of the body to foreign materials .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation